Sosialiasi Pengadaan Bahan dan Alat Kerja Furniture Untuk Meningkatkan Kelancaran Usaha Perusahaan - Julito, Kiko Armenita; Yani, Ari Soeti; Hosea, Amos Julian (Jurnal Pemberdayaan Nusantara, 2023)
The purpose of this research is to find out whether the Procurement of Materials and Work Equipment that is implemented by IdeSign Interior Design & Build at Pegadungan Kalideres, West Jakarta is optimal and can increase insight into the importance of the process of Procurement of Work Materials and Equipment at IdeSign Interior Design and Furniture Company. This research was conducted through direct observation to the location, namely Pegadungan Kalideres, West Jakarta. Data collection was carried out by field observations and interviews with the Supervisor and CEO of IdeSign Interior Design & Build.Limited knowledge related to differences in the quality of Materials and Working Tools from various brands or brands used is a problem faced in managing a furniture business, it is necessary to identify the quality specifications of a brand or brand, besides that differences in price and availability of goods affect the process of providing materials to evaluate various types of decision-making and raw materials remain available when needed.